2021
DOI: 10.1007/s12072-020-10132-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonalcoholic fatty liver disease in mental disorder inpatients in China: an observational study

Abstract: Background and Purpose Non-alcoholic fatty liver disease (NAFLD) is becoming the most common liver disease in China. However, the understanding of NAFLD prevalence among Chinese mental disorder inpatients remains insufficient. We aim to investigate the prevalence of NAFLD among mental disorder inpatients in Beijing, China. Methods In this observational study, we included 66,273 mental disorder inpatients between 2014 and 2018, including inpatients with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…While studies have been conducted to describe the relationship between depression and NAFLD, previous literature has reported conflicting results, varying from a strong association ( 17 , 18 ) to no association ( 19 , 20 ). A study involving a database of 567 patients with biopsy-proven NAFLD estimated that 67.5% of patients had depressive symptoms and showed that they were associated with histological severity of NAFLD ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…While studies have been conducted to describe the relationship between depression and NAFLD, previous literature has reported conflicting results, varying from a strong association ( 17 , 18 ) to no association ( 19 , 20 ). A study involving a database of 567 patients with biopsy-proven NAFLD estimated that 67.5% of patients had depressive symptoms and showed that they were associated with histological severity of NAFLD ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…49.5% (100/202) of the schizophrenia group had steatosis on AUSS, compared with 20.1% (30/149) of the control group. Although NAFLD prevalence amongst inpatients with schizophrenia was not as high (22.44%) as in the aforementioned studies, in another 2021 Chinese study[ 19 ] comprising 66,273 patients with “mental disorders”, it was still higher than amongst those with bipolar affective disorder (17.89%), depressive disorder (12.62%) and other mental disorders (12.99%) and was demonstrated to be associated with antipsychotic treatment.…”
Section: Chronic Liver Diseasementioning
confidence: 80%
“…However, after 50-60 years of age, NAFLD occurs at a higher rate in women [15,16]. In the Ma et al study, concerning the Asian population, a higher incidence of NAFLD was associated with schizophrenia and bipolar disorder to a greater extent than with other psychiatric disorders and also, like the above mental disorders, was correlated with the components of MetS [17]. In the population-cohort study, also in relation to the Asian population, Hsu et al observed, that patients with schizophrenia showed significantly higher morbidity and incidence of chronic liver disease than general population, and diabetes was a risk factor for developing chronic liver disease in patients with schizophrenia [1].…”
Section: Epidemiology Of Nafldmentioning
confidence: 93%
“…Almost ¾ of them were treated with neuroleptics. The use of antipsychotic drugs was associated with a 1.46 times higher incidence of NAFLD compared to no use of neuroleptic [17].…”
Section: Antipsychotic Drugsmentioning
confidence: 95%
See 1 more Smart Citation